The staff–student co-design of an online resource for pre-arrival arts and humanities students. (April 2022) - Woods, Kathryn; Homer, Damien
Successful induction has been evidenced to strengthen students' learning, engagement and feelings of belonging. Technology offers opportunities for enhancing the student induction experience, especially pre-arrival, but has been under-utilised. This article provides an evaluation of an online induction learning resource for pre-arrival students in the Faculty of Arts at the University of Warwick in 2019. There will be particular focus on the method of co-designing the resource with a group of current students. The article will demonstrate how online learning resources for pre-arrival students can support successful induction. It argues that co-designing digital student experience resources in collaboration with students aids the development of materials that students find engaging and that co-design has a range of benefits for staff and students who are involved in the process.